Importance of the personal collection of the Michael Z. Vinokouroff library as a resource of research - Rufova, Elena Stepanovna (2020)
Within the framework of this article, an attempt is made to study the information potential of documents from the personal collection of Mikhail Z. Vinokouroff, stored in the Alaska State Library, their source analysis will determine the directions of their further scientific use. Numerous documents and diaries, letters and notes, books and photographs of the archival fund of the bibliophile are the objects of attention of scientists and researchers of the issues of the Russian Orthodox Church, historians, bibliographers, linguists, literary scholars. As a result of the study, the main directions of the effective scientific use of documents from the personal archive of M.Z. Vinokouroff. In addition to studying unpublished diaries and notes of a bibliophile, the collection contains letters from St. Innokentii Veniaminov, as well as documents reflecting the political and literary life of Yakutia in the first third of the 20th century.